2012
DOI: 10.1002/rcs.1426
|View full text |Cite
|
Sign up to set email alerts
|

Robotic assistance may reduce conversion to open in rectal carcinoma laparoscopic surgery: systematic review and meta‐analysis

Abstract: This meta-analysis of available non-randomized studies suggests that conversion to open rate may be reduced when using RARS instead of LARS for rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 41 publications
3
33
4
Order By: Relevance
“…For the laparoscopic groups, these data varied from 12.2 % [12] to 20 % [11]. However, no significant differences were found between groups, either by studies or by meta-analysis of pooled data [23,29]. In the present study, we found no significant differences in terms of complications between laparoscopic and robotic TME, although there were numerically fewer complications in the robotic group.…”
Section: Discussioncontrasting
confidence: 71%
“…For the laparoscopic groups, these data varied from 12.2 % [12] to 20 % [11]. However, no significant differences were found between groups, either by studies or by meta-analysis of pooled data [23,29]. In the present study, we found no significant differences in terms of complications between laparoscopic and robotic TME, although there were numerically fewer complications in the robotic group.…”
Section: Discussioncontrasting
confidence: 71%
“…In rectal carcinoma, a meta-analysis indicates that the convention to open rate is lower for robotic assistance than the traditional LS (OR ¼ 0.31, 95% CI: 0.12 to 0.78), which is consistent with our results in rectal adenocarcinoma subgroup (OR ¼ 0.17, 95% CI: 0.06 to 0.46), but the EBL is not different between the two approaches. 32 This result seems inconsistent with our findings, however, we should note that in Ortiz-Oshiro's study, there were only two authors who reported the relevant data regarding EBL, 32 which might cause publication bias. Boggi et al provide positive evidence that laparoscopic robot-assisted total pancreatectomies significantly reduce the mean blood loss compared with open total pancreatectomies (220 vs. 705 mL, p ¼ 0.004).…”
Section: Discussioncontrasting
confidence: 97%
“…The overall results compare favorably with those of the standard approaches . Even more interesting, less conversion to open has been reported after robotic low anterior resections when compared with laparoscopy .…”
Section: Introductionmentioning
confidence: 63%